Pusat Kebudayaan Papua Selatan - Santibo Bois Ruimassa; Biatma Syanjayanta; Atiza Nurhuzna (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2019)
As a form that refuses to be accepted and supports the culture of the ancestors so that they feel concerned and that simplifies the era of globalization in the lives of people in Papua in the South that have been approved in relation to the areas where the community is increasing the work of modern culture. In this case, the method of collecting data used in this research is Observation, observation is the activity of direct monitoring of an object by using all five senses. Interview / Interview, interview is a data conversion technique used by researchers to be able to seek help- verbal involvement through direct questions and face to face with people who can give information. Documentation, this method is used to obtain data relating to museums and other data that can support this research, namely by searching literature from books (literature) and taking pictures.